APLIKASI TEKNIK MICRONIZING JAGUNG KUNING PADA RANSUM ISA BROWN LEGHORN TERHADAP MASA SIMPAN TELUR - Yoga Setyo Utomo; Zakaria Husein Abdurrahman; Eudia Christina Wulandari (Universitas Boyolali, 2021)
This study aims to determine the effect of the yellow corn micronizing technique on the feed ration and shelf life of chicken eggs on the quality of egg contents. This research was conducted from May to June 2021 at the laying hens' farm in Sidorejo Village, Musuk District, Boyolali Regency. The research material was 54 laying hens aged 21 weeks. In this study, milled corn was used as feed ingredients with micronizing, concentrate, and bran techniques. The equipment used is in the form of a semi-open house battery cage with 54 bulkheads, as well as a place to feed and drink. Each bulkhead contained one laying hen and was divided into three treatments with each treatment consisting of 18 laying hens Isa brown leghorn. The refining tool used for yellow corn rations is a milling machine with a temperature of 140-180oC. Corn is ground into 3 (three) levels of corn particles, namely fine grain, medium grain, and coarse grain. All research data were analyzed using the variance procedure. If there is a significant difference (P < 0.05), it is continued with the Duncan Multiple Range Test at the 5% level. The results showed that there was a significant effect on all parameters, namely egg white index, egg yolk index, Haugh index, ration consumption, and egg weight. The provision of corn with different forms gave a significant effect on each parameter of observation at different storage periods. The conclusion of this study is that there is an effect of the yellow corn micronizing technique on the ration on the consumption of the ration. The yellow corn micronizing technique and the shelf life of eggs also affect the quality of the egg contents